George Montfort Gilchrist family papers - Gilchrist, George Montfort
Correspondence, school records, literary and commencement programs, poetry, and Gilpin family genealogical material. Much of the correspondence is between Gilchrist, who served with the 3rd Indiana Cavalry in Maryland, Pennsylvania, and Virginia during the Civil War, and his wife, Mollie Gilpin Gilchrist; other letters are between Mollie and her brothers, Samuel J. V. B. Gilpin, of the 1st Indiana Cavalry, and E. N. Gilpin, of the 3rd Iowa Cavalry. Includes material relating to Hanover College, Hanover, Indiana.
U.S. Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Gilchrist family; Gilchrist, Mollie Gilpin; Gilpin family; Gilpin, E. N; Gilpin, Samuel J. V. B; United States. -- Army. -- Indiana Cavalry Regiment, 1st (1861-1864); United States. -- Army. -- Indiana Cavalry Regiment, 3rd (1861-1865); United States. -- Army. -- Iowa Cavalry Regiment, 3rd (1861-1865); Hanover College; Maryland -- History -- Civil War, 1861-1865.; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Virginia -- History -- Civil War, 1861-1865.; Army officers